Development of new N -4-[(7-Chloro-5-methylpyrrolo[2,1-f ] [1,2,4]triazin-4-yl)oxy]-3-fluorophenylbenzenesulfonamide analogues: exploring anticancer potential through MerTK inhibition - Sathe, Balaji Dashrath; Meenakshi, Meenakshi; Murti, Yogesh; Mane, Madhav Shivaji; Pandey, Sarvesh Kumar; Mahajan, Shriya; Rawat, Pramod; Kandhari, Harsimrat; Goel, Kapil Kumar; Dwivedi, Ashish Ranjan; Rathod, S. V. (Synlett, 2025)
Mer proto-oncogene tyrosine-protein kinase (MerTK), a part of the TAM (TYRO3, AXL, and MerTK) family, is directly correlated with metastasis and various types of cancers. The inhibition of this receptor is a promising strategy for more-effective chemotherapy. Considering the pharmacophoric features of the active domain of MerTK and the structural characteristics of the investigational drug BMS794833, we designed five new N -{4-[(7-chloro-5-methylpyrrolo[2,1- f ][1,2,4]triazin-4-yl)oxy]-3-fluorophenyl}benzenesulfonamide analogues. In cytotoxicity studies, one of the analogues displayed a significantly higher cytotoxicity than cisplatin. It showed IC50 values of 2.09, 1.96, and 3.08 mu M against A549, MCF-7, and MDA-MB-231 cancer cell lines, respectively. In drug metabolism and pharmacokinetic studies, it was the most stable analogue and displayed a moderate MerTK inhibitory potential. Molecular-docking studies were performed to corroborate the MerTK inhibition, and the same analogue achieved the most significant docking score (-12.33 kcal/mol). Docking interactions demonstrated that the imine and amine group of the 3-chloropyridine moiety of BMS794833 formed hydrogen bonds with the main chain of the ATP pocket residue Met674, while the oxygen atoms of the 4-oxo-1,4-dihydropyridine-3-carboxamide moiety established hydrogen bonds with the Lys619 and Asp741 amino acid residues of the allosteric pocket of MerTK protein. These promising results provide evidence that the N -{4-[(7-chloro-5-methylpyrrolo[2,1- f ][1,2,4]triazin-4-yl)oxy]-3-fluorophenyl}benzenesulfonamide pharmacophore can give potential insights into the development of new MerTK inhibitors.
Keywords: cancer chemotherapeutics; kinase inhibitors; metabolic studies; pyrrolotriazines; sulfonamides

Dual inhibition of AXL and MER kinase: scope for lung and breast cancer therapeutics - Sathe, Balaji Dashrath; Kumari, Pratibha; Kumar, Hemant; Mane, Madhav Shivaji; Mudududdla, Ramesh; Baell, Jonathan; Kumar, Roshan; Singh, Shareen; Pawar, D. K.; Kommi, Damodara N.; Bushi, Ganesh; Pathak, Prateek; et al. (Bioorganic Chemistry, 2025)
Cancer cells use multiple survival pathways for continuous proliferation, survival, and growth. Recent anticancer drug discovery commonly focuses on a single target that maintains key cancer cell survival mechanisms, where typically, this is a cellular enzyme that inhibits DNA replication, inducing cell damage and apoptosis. Since drugs that act on a single target may be more susceptible to the development of resistance, the search for polypharmacotherapeutics is becoming increasingly popular to defeat drug-resistant cancer cells. Receptor tyrosine kinases (RTKs) family members, AXL and MER, have been identified as important cancer targets and found to be overexpressed and associated with various forms of cancers, such as lung and breast cancers. This review has focused on the dual inhibition of AXL and MER kinases as a strategy for treating lung and breast cancer. The roles of these two kinases in non-small cell lung cancer (NSCLC) are such that dual inhibition would be therapeutically complementary, with MER inhibition more fully blocking tumor growth while AXL inhibition encourages chemosensitivity. Hence, treatment strategies targeting both of these RTKs may be more effective and beneficial than singly targeted agents, and a dual AXL/MER inhibitor is a potential therapy for NSCLC along with breast cancer. This review highlights the preclinical and clinical development of dual AXL and MER kinase inhibitors as lung and breast cancer treatments and the prospects for their future progression.
Keywords: AXL; Breast cancer; Cancer therapy; MER; Multi-kinase inhibitors; NSCLC targeted therapy